2017
DOI: 10.1038/srep46524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese Medicine as Adjunct Medication for Adjuvant Chemotherapy Treatments of Non-Small Cell Lung Cancer Patients

Abstract: The aim was to evaluate the effects of traditional Chinese medicine (TCM) as a combination medication with adjuvant chemotherapy on postoperative early stage non-small cell lung cancer (NSCLC) patients. The 314 patients with completely resected stage IB, II or IIIA cancers were assigned into vinorelbine plus cisplatin/carboplatin (NP/NC) (control, n = 158) and NP/NC with additional TCM (intervention, n = 156) groups. The primary endpoint was QOL scores; secondary endpoints were the toxicity and safety of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 60 publications
1
37
0
Order By: Relevance
“…It was revealed that compared with the patients receiving ACT alone, those receiving Chinese medicine + ACT enjoyed a longer time without relapse or metastasis [10]. Our previous study showed that Chinese herbal medicines based on syndrome differentiation were able to improve the symptoms, including nausea, fatigue, pain and dry mouth, and also alleviate some chemotherapy-related side effects [11,12].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…It was revealed that compared with the patients receiving ACT alone, those receiving Chinese medicine + ACT enjoyed a longer time without relapse or metastasis [10]. Our previous study showed that Chinese herbal medicines based on syndrome differentiation were able to improve the symptoms, including nausea, fatigue, pain and dry mouth, and also alleviate some chemotherapy-related side effects [11,12].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…However, these treatments are also limited to a certain extent. Clinically, the effectiveness of chemotherapy alone is not completely satisfactory due to the potential side effects and adverse reactions that affect the quality of life (QOL) and seriously inhibit the immune function of patients [9]. Hence, drugs that exhibit clinical efficacy and promote immune function, improve QOL, and alleviate side effects and adverse reactions may be preferable for advanced NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study reported that the adverse events from CHM combined with chemotherapy had a lower overall incidence than those from chemotherapy alone, especially in the improvement of symptoms (e.g., pain, diarrhea, and hemoptysis). However, it was also observed that CHM could increase the incidence of nausea and vomiting in the combined chemotherapy [20].…”
Section: Introductionmentioning
confidence: 99%